Synthesis and antimicrobial activities of hydrazones derived from 4-hydroxy-3-nitrobenzaldehyde - Nguyen Thi Ngoc Mai; Trinh Thi Huan; Le Thanh Van; Nguyen Vu Huan; Duong Quoc Hoan (Vietnam Journal of Science and Technology, 2023)
A method using transistors based on semiconducting carbon nanotubes were developed for the real-time monitoring of the electrophysiological responses of individual cells to histamine stimulation. Transistors with one or three floating electrodes were utilized to evaluate histamine-induced Ca2+ influx into Hela cells via recording the conductance changes of the transistors. The Hela cells were directly cultured on the semiconducting carbon nanotube junction area of the transistors. The Ca2+ influx resulted from the activation of histamine H1 receptors embedded on the cell membranes by histamine, which generated a temporary negative potential at the gap between the cell and the transistor. The addition of histamine therefore increased the conductance of the p-type transistors. Moreover, the antihistamine effects of chlorpheniramine on histamine-induced Ca2+ influx were also investigated using a transistor including three floating electrodes. The data showed that chlorpheniramine partial reduced the increase in the conductance of the transistor during the addition of histamine, indicating the antihistamine activity of chlorpheniramine. Especially, only a single transistor was applied to repeat the measurements of the responses of multiple Hela cells pretreated with chlorpheniramine to histamine stimulation. This allows us to acquire data without being suffered from device-to-device variations, implying that our method would be a simple yet powerful one for applications of nanoscale biosensors for electrophysiological studies.